Sistem Informasi Pengolahan Nilai Rapor Dan Prediksi Penjurusan Menggunakan Naive Bayes Berbasis Web Di SMAN 5 Bangko Pusako - Ramadani Umri; Dahliyusmanto Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
SMAN 5 Bangko Pusako is one of the senior high school that has implemented 2013 Curriculum in its assessment standards. However, due to evaluation standard of 2013 curriculum is more complicated so it makes teachers feel difficulty in marking process. In addition, the marking process in SMA N 5 Bangko Pusako still uses Microsoft Excel where every subject teacher has their own grades file, then the homeroom teacher will unite all the grades of the subject teacher and reprocess it to be used as a report card. The lack of integration of marking process between subject teacher and homeroom teacher makes the marking process takes a long time, so we need a web-based marking process information system that can facilitate the work of teachers in marking process in 2013 curriculum is needed. This information system is created by using PHP Programming Language and MySQL as database. The results of this study are information systems that manage web-based values that apply 2013 curriculum assessment standards so teachers do not feel difficulty in calculating grades. In addition, this information system can integrate and calculate all grades from the subject teacher and homeroom teacher, then the final grades can be printed directly into report cards. In this system, Naive Bayes Method is also used for prediction of students’ field. Function to predict are made by using RapidMiner, which is provide an accuracy of 95,24% with an error rate of 4,76%. Keywords : Information System, 2013 Curriculum, Marking Process, PHP, MySQL